2004
DOI: 10.2527/2004.8292568x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the feeding value of South Dakota-grown field peas (Pisum sativum L.) for growing pigs12

Abstract: Four experiments were conducted to investigate the feeding value of South Dakota-grown field peas (Pisum sativum L.) for growing pigs. In Exp. 1, 96 pigs (initial BW = 22 +/- 3.35 kg) were allotted to four treatment groups (four pigs per pen, six replicate pens per treatment) and fed growing (0.95% Lys) and finishing (0.68% Lys) diets containing 0, 12, 24, or 36% field peas (as-fed basis). There were no differences among the treatment groups in ADG, ADFI, or G:F. Likewise, there were no differences in backfat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 25 publications
12
45
0
1
Order By: Relevance
“…Performance characteristics such as feed conversion, lean meat and backfat were not influenced by the inclusion of peas and extruded peas in the diet. These results are in close agreement with earlier published data indicating that no differences in pig performance are recorded if pigs are fed diets containing field peas or pea-based diets (Stein et al, 2004(Stein et al, , 2006Petersen and Spencer, 2006).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Performance characteristics such as feed conversion, lean meat and backfat were not influenced by the inclusion of peas and extruded peas in the diet. These results are in close agreement with earlier published data indicating that no differences in pig performance are recorded if pigs are fed diets containing field peas or pea-based diets (Stein et al, 2004(Stein et al, , 2006Petersen and Spencer, 2006).…”
Section: Resultssupporting
confidence: 93%
“…Replacing soybean Table 5 shows the two-factor analysis of variance aimed at indicator growth and fattening of pigs between groups and sex. Pea (Pisum sativum L.) is a good, traditional source of nitrogen and energy for pigs due to the high digestibility and palatability (Fan et al, 1994;Chrenková et al, 2001) without deterioration of health, production and carcass and meat quality (Thacker 2002;Stein et al, 2004Stein et al, , 2006, which is in agreement with presented results.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, the pigs fed the RP and RF diets ate similarly to the pigs fed the CTR overall the trial but RF pigs grew better than CTR animals. Recently, Stein et al (2004) and Prandini et al (2005) have shown that field peas may be included from 15 to 20% in diets offered to nursery pigs. At these concentrations, no negative effect on pig performance has been recorded.…”
Section: Animal Performance and Carcass Characteristicsmentioning
confidence: 99%
“…Peas are characterrized by lower aminoacid content compared to soybean meal, and a lower digestibility of energy than corn (Stein et al, 2004). In growing -finishing pigs there is no limitation on dietary inclusion levels, but in weaned piglets results are less conclusive.…”
Section: Introductionmentioning
confidence: 99%